Zoea Syndrome (ZS) pada Larva Udang Vannamei (Litopenaeus vannamei) - Rubiyanto Widodo Haliman (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
White shrimp (Litopenaeus vannamei) culture in Indonesia has been well developed since 1999. Among the problems occurred during the culture period in the hatchery, Zoea Syndrome (ZS) is the most serious. An observation has been done to determine the prevalence and the clinical signs of this syndrome. Nauplii were collected from hatcheries in East Java (3 hatcheries) and Central Java (1 hatchery) and subject to PCR test in order to obtain TSV free nauplii. The results showed that TSV free nauplii could also be infected by ZS, where the prevalence could reach 100%. There was also a possibility that Vibrio sp. was involved in ZS infection.